125x+3=52x+4

Simple and best practice solution for 125x+3=52x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 125x+3=52x+4 equation:


Simplifying
125x + 3 = 52x + 4

Reorder the terms:
3 + 125x = 52x + 4

Reorder the terms:
3 + 125x = 4 + 52x

Solving
3 + 125x = 4 + 52x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-52x' to each side of the equation.
3 + 125x + -52x = 4 + 52x + -52x

Combine like terms: 125x + -52x = 73x
3 + 73x = 4 + 52x + -52x

Combine like terms: 52x + -52x = 0
3 + 73x = 4 + 0
3 + 73x = 4

Add '-3' to each side of the equation.
3 + -3 + 73x = 4 + -3

Combine like terms: 3 + -3 = 0
0 + 73x = 4 + -3
73x = 4 + -3

Combine like terms: 4 + -3 = 1
73x = 1

Divide each side by '73'.
x = 0.01369863014

Simplifying
x = 0.01369863014

See similar equations:

| 0.4p-2=0.8p-3 | | 8x+2(x-9)=82 | | -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y |

Equations solver categories